6x−12+2x=3+8x−15
Simplify:
6x+−12+2x=3+8x+−15
(6x+2x)+(−12)=(8x)+(3+−15)(Combine Like Terms)
8x+−12=8x+−12
8x−12=8x−12
Subtract 8x from both sides.
8x−12−8x=8x−12−8x
−12=−12
Add 12 to both sides.
−12+12=−12+12
0=0
The real numbers are the only solution we can have.
130 i think let me know if this is right
Answer:
900
Step-by-step explanation:
you just see if by the number, if the number is 6 and up your round over and it would become 950 but the number is lower so you make it 900.
The answer is 2x^2-3x-2.
To solve this, you take f(x)-g(x) which is 2x^2-5-3x+3. This simplifies to 2x^2-3x-2.
Answer:
6x^2*(x+4)
Step-by-step explanation:
hope this helps! :)